2010
DOI: 10.1210/en.2010-0754
|View full text |Cite
|
Sign up to set email alerts
|

Apelin Mediates the Induction of Profibrogenic Genes in Human Hepatic Stellate Cells

Abstract: apelin mediates some of the fibrogenic effects triggered by AII and ET-1, thus suggesting that apelin could be an important mediator of fibrogenesis in human liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 27 publications
3
73
0
2
Order By: Relevance
“…Apelin has inhibitory activity against human immunodeficiency virus infection (3,58), reduces proinflammatory cytokine production in spleen cells (13) and in the mouse cardiovascular system, and lowers abdominal aortic aneurysm formation by reducing disease-associated vascular inflammation (23). Recent reports demonstrate an emerging role for the apelin-APJ axis in regulation of liver, kidney, and heart fibrosis (24,29,32,45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apelin has inhibitory activity against human immunodeficiency virus infection (3,58), reduces proinflammatory cytokine production in spleen cells (13) and in the mouse cardiovascular system, and lowers abdominal aortic aneurysm formation by reducing disease-associated vascular inflammation (23). Recent reports demonstrate an emerging role for the apelin-APJ axis in regulation of liver, kidney, and heart fibrosis (24,29,32,45).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the inhibitory effect of apelin on pancreatic fibrosis, hepatic fibrosis is stimulated by apelin exposure (24). In human liver disease, apelin seems to mediate profibrogenic gene induction promoted by ANG II and endothelin-1 in hepatic stellate cells.…”
Section: G146 Apelin and Pancreatitismentioning
confidence: 92%
See 1 more Smart Citation
“…Apelin was found to be highly expressed by HSCs and in the same study the use of an antagonist of the apelin receptor was reported to inhibit not only angiogenesis but also hepatic fibrosis. In addition, exposure of LX-2, a human HSC line, to recombinant apelin resulted in an increased synthesis of type I collagen as well as of PDGF-β receptor [77]. Moreover, available data on LX2 cells at present suggest that apelin expression can be up-regulated by angiotensin II and endothelin-1 [77] whereas expression of the apelin receptor APJ is positively stimulated by exposure to hypoxia and lipopolysaccharide [78].…”
Section: Adipokinesmentioning
confidence: 97%
“…On the other hand, CB2 receptor agonism shows opposite antifibrogenic and anti-inflammatory effects in hepatic and nonhepatic tissue (Muñ oz-Luque et al, 2008;Akhmetshina et al, 2009) and protects against liver ischemia-reperfusion injury (Horvá th et al, 2011). Previous studies by our laboratory have demonstrated that the proangiogenic peptide, apelin (AP), is up-regulated in HSCs of patients with cirrhosis (Melgar-Lesmes et al, 2010). Furthermore, this peptide behaves as a paracrine mediator of fibrogenesis-related gene induction in human HSCs (Melgar-Lesmes et al, 2010), and apelin receptor (APJ) blockade has shown to be effective in reducing hepatic fibrosis and angiogenesis in rats with cirrhosis (Principe et al, 2008).…”
Section: Introductionmentioning
confidence: 99%